Hubungan Keterlibatan Ayah Dengan Perilaku Seksual Pranikah Pada Remaja - Muthiya Fatma Pulungan; Winida Marpaung; Nur Hidayah Darajat; Rina Mirza (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
Premarital sexual behavior among adolescents has become an important issue due to its potential psychological, social, and educational impacts. One factor that may reduce adolescents’ involvement in risky sexual behavior is father involvement, which includes emotional support, supervision, communication, and active participation in children’s development. This study aimed to examine the relationship between father involvement and premarital sexual behavior among adolescents at Immanuel Christian Senior High School in Medan City. This research employed a quantitative correlational design. The participants consisted of 105 male and female students who were currently involved in dating relationships and were selected using purposive sampling techniques. Data were collected through Likert-type scales, including a 39-item premarital sexual behavior scale and a 40-item father involvement scale. Data analysis was conducted using Pearson Product-Moment correlation with the assistance of IBM SPSS Statistics version 26. The results showed a significant negative relationship between father involvement and premarital sexual behavior, with a correlation coefficient of r = -0.239 and a significance value of p = 0.014 (p < 0.05). These findings indicate that adolescents who experience higher levels of father involvement tend to show lower engagement in premarital sexual behavior. Low father involvement is associated with a greater tendency toward risky sexual behavior among adolescents. Father involvement contributes to adolescents’ behavioral regulation through guidance, supervision, and emotional closeness. In conclusion, father involvement plays an important protective role in reducing premarital sexual behavior among adolescents. This study highlights the importance of strengthening fathers’ active participation in adolescent development.